Decanter Brand Selection Using Multi-Criteria Decision Making: A Case Study - Nasution, Fadlin Qisthi; Nasution, Muhammad Ansori; Rivani, Meta (Institute of Research and Community Outreach - Petra Christian University, 2024)
Decanters play a crucial role in Palm Oil Mills by separating the oil phase from the sludge underflow in continuous settling tanks during the clarification process. Given the significance of decanters and the multitude of manufacturers, this study focuses on a comprehensive evaluation of three-phase decanter brands selection. Utilizing the analytic hierarchy process, the research explores the nuanced criteria of economics, technical aspects, and service quality for brand selection. Sub-criteria include operational cost, price, overhaul cost, emulsion content, oil losses, capacity, distance to buffer tank, electricity consumption, service scheme, guarantee, spare part availability, and workshop location. The alternatives considered are common decanter brands in Indonesia: Alfa Laval, IHI, Flottweg, and Westfalia. Using Expert Choice®, the analysis identifies Flottweg as the optimal decanter brand based on performance, particularly excelling in service criteria with a priority weight of 0.336. Sensitivity analysis indicates that for IHI to be considered the first option, technical and economic criteria must be prioritized above 56.5% and 50.0%, respectively. This study also concluded that technical and service aspects are equally important in decision-making for the decanter brand in POM A, surpassing economic ones, with service aspects as the critical factor in decanter brand decision-making.